2010
DOI: 10.1111/j.1365-2958.2010.07460.x
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the LEE1 operon regulatory region of enterohaemorrhagic Escherichia coli O157:H7 and activation by GrlA

Abstract: SummaryExpression of the genes in the locus of enterocyte effacement (LEE) in enterohaemorrhagic Escherichia coli is primarily co-ordinated by expression of the LEE1 operon. GrlA is a LEE-encoded transcription regulator that has been proposed to be involved in the regulation of expression of the LEE1 operon. We describe a simple plasmid-based system to investigate the LEE1 operon regulatory region and to study GrlA-dependent effects. We report that GrlA can activate transcription initiation at the LEE1 P1 prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 50 publications
4
53
0
Order By: Relevance
“…In this manner, expression of nleA will be induced mostly under conditions that allow the expression of Ler and, thus, of the LEE genes, where it overcomes H-NS repression by competitively binding to a region that overlaps the H-NS binding sites at the LEE promoters. Consistent with a recent report (82), GrlA was also required for full activation of nleA, most likely in an indirect manner as GrlA's role in the regulation of LEE genes is due to its function as a positive regulator of ler expression (2,18,37,39,42,50).…”
Section: Discussionsupporting
confidence: 88%
“…In this manner, expression of nleA will be induced mostly under conditions that allow the expression of Ler and, thus, of the LEE genes, where it overcomes H-NS repression by competitively binding to a region that overlaps the H-NS binding sites at the LEE promoters. Consistent with a recent report (82), GrlA was also required for full activation of nleA, most likely in an indirect manner as GrlA's role in the regulation of LEE genes is due to its function as a positive regulator of ler expression (2,18,37,39,42,50).…”
Section: Discussionsupporting
confidence: 88%
“…Differential regulation of the LEE among EHEC strains 86-24, EDL933, and Sakai has been observed in studies examining the roles of RpoS and GrlA in EHEC virulence (18,37,38,49,80,86). Moreover, Islam et al reported that the ler P1 promoter was the major promoter activating LEE expression in EHEC strains Sakai and EDL933 (37), whereas other studies have found that the ler P2 promoter was the major promoter in EHEC strain 86-24 (74, 78). Islam et al suggested that the differences are likely due to the genetic backgrounds of the strains and/or the exact fusions and measurement conditions used in the experimental design (37).…”
Section: Discussionmentioning
confidence: 93%
“…GrlA is a positive regulator of LEE1, and GrlR binds directly to GrlA to block its activity (24). Under inducing conditions, the GrlR repression is removed, likely by its targeting to degradation by ClpXP (25), allowing the establishment of a positive feedback loop between GrlA and Ler (9,10). This mechanism provides a rationale for the relatively high level of basal expression of LEE7 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…P LEE1 is repressed by H-NS at 27°C, but upon shifting of the culture to 37°C, P LEE1 is activated and no longer repressed by H-NS. This LEE1 activation is mediated by PerC and/or GrlA, which are redundant positive regulators of P LEE1 (8,9). PerC is encoded by a large plasmid, and GrlA is encoded by a bicistronic operon within the LEE (LEE7) (10).…”
mentioning
confidence: 99%